Epilepsy: classification of remission of seizures and disease, their clinical and psychological and neurophysiological rationale, the questions of diagnostics and pharmacotherapy - S. A. Gromov; N. A. Sivakova; E. A. Korsakova; M. F. Kataeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Clinical and neurophysiological studies was conducted in 426 patients with epilepsy with longterm (more than 8 years) remission of seizures. It is established that the control of seizures accompanied by epileptic activity regression on EEG to full health compensation for 5-8 years at 45% of the observed, that allows to solve questions of completion of treatment.